Number 14 (March 1983) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1983)
Fishes of the South Fork of the Kentucky River with Notes and Records from Other Parts of the Drainage. By B.A. Branson and D.L. Batch, 16 pp.
Keywords: south fork; fishes; kentucky river